The ghost illusion [large type] - Martin, Kat (Thornkdike Press, a part of Gale, a Cengage Company, 2023)
"Eve St. Clair desperately needs help sorting reality from her fearful imaginings when ghostly voices seem to haunt the Victorian house in Sunderland, England, that she inherited from her uncle. Since the deaths of his wife and daughter, Seattle billionaire Ransom King has devoted himself to researching parapsychology and debunking the frauds who prey upon the bereaved. But Eve is a psychologist herself, clearly sane, and her sincerity is palpable. King senses a very real danger stalking the beautiful divorcee. As his interest in her case turns deeply personal, he will move heaven and earth to uncover the truth - no matter how shocking - and save the woman he loves" --